Neonatal cardiac hypertrophy: A rare case of clinically suspected and genetically confirmed mitochondrial disorder presenting as hypertrophic cardiomyopathy - Sushil Azad,; Ashish Banpurkar,; S Radhakrishnan,; Ankit Garg, (Indian Journal of Case Reports, 2021)
Infants presenting with ventricular hypertrophy in the absence of structural heart disease causes can be either genetic, metabolic, or storage disorders. Familial hypertrophic cardiomyopathy is very rare in the neonate. We present a rare case of infantile cardiomyopathy with clinical suspicion of mitochondrial disorder confirmed genetically to have a disorder of mitochondrial oxidative phosphorylation with both parents as a carrier of the recessive gene to highlight the importance of detail genetic evaluation of all neonates presenting with ventricular hypertrophy.